Reflections on the Historical Development of the Content of Geography Textbooks in Jordan 1921-2021 - Tawalbeh, Hadi Mohamad; Khasawneh, Majdi Abdallah (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed at reflecting on the historical development of the content of geography books in Jordan from 1921-2021. Methods: To achieve the objectives of the study, the analytical descriptive approach was adopted, by preparing a note card for each book of geography that includes indicators monitored in each book. The study population included all geography books approved by the Ministry of Education over the period of 1921-2021, which are available in the Textbook Museum. Results: The results of the study showed the geographical topics presented to students in each grade and educational stage of the general education stages, the features of development through the historical eras that the Hashemite Kingdom of Jordan went through. The results also showed the common geography books that targeted more than one category such as males and females, or those books that were prepared for lower and higher grades, or those shared between the school stage and the post-school stage. The results also indicated the mechanisms of printing books, the features of the evaluation process, how to handle typographical errors, and approved translated books, in addition to showing the image of women and maps in them. Conclusions: The study highlights the necessity of reinstating the social studies subject for Jordan's first three grades, which was discontinued over seven years ago. Additionally, it suggests incorporating key themes such as the geography of Arab countries, along with topics in geology and astronomy, particularly those relevant to the early years of Jordan's establishment.